Energetics and Alfvénic Coupling of a Poleward Boundary Intensification: A Polar Case Study. Issue 8 (14th August 2020) - Keiling, Andreas; Wygant, John; Fillingim, Matthew; Trattner, Karlheinz J.
Abstract: The poleward boundary intensification (PBI) is a common appearance at the poleward boundary of the auroral bulge and auroral oval. The PBI presented here occurred during the expansion phase of a small substorm with an auroral surge power of 6.5 GW. The auroral power of the PBI (1.1 GW) was ~17% of this value. The largest powers above the nominal auroral acceleration region at 5  R E geocentric were carried by Alfvén waves (1.7 GW) and Alfvénic electrons (0.7 GW), sufficient to account for the conjugate PBI auroral power. In contrast, the conjugate quasistatic, field‐aligned current power (<0.3 GW) was not sufficient. Observed correlation between quasiperiodic Alfvénic pulses and auroral modulations strengthens our conclusion that the electromagnetic magnetosphere‐ionosphere coupling of the PBI was dominantly Alfvénic, as opposed to electrostatic, thus causing Alfvénic aurora. Key Points: Quasiperiodic magnetotail Alfvén wave pulses drive correlated PBI luminosity modulations Magnetosphere‐ionosphere coupling of PBI is dominantly Alfvénic, as opposed to electrostatic PBI power estimates are compared with streamer power estimates